Some aspects of the biology of Euplotes focardii, a new ciliates species from Antartica - VALBONESI A; LUPORINI P; FELICI, Alberto (1991)
some aspects of the biology of Euplotes focardii, a new ciliates species from Antarticahave been investigated, with particular respect to the molecular mechanisms of intraclonal recognition